2013
DOI: 10.3109/10428194.2013.847936
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA let-7f is down-regulated in patients with refractory acute myeloid leukemia and is involved in chemotherapy resistance of adriamycin-resistant leukemic cells

Abstract: Leuk Lymphoma Downloaded from informahealthcare.com by University of Otago on 07/07/15For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…miRNA also plays an important role in tumorigenesis. In recent years, more and more studies have reported abnormal miRNA expression in drug-resistant cell lines such as cancers of the breast [7], ovary [8], and lung [9], as well as leukemia [10]. Through directly regulating key target genes, miRNAs can cause phenotypic alterations in tumor cells, thereby mediating tumor resistance to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA also plays an important role in tumorigenesis. In recent years, more and more studies have reported abnormal miRNA expression in drug-resistant cell lines such as cancers of the breast [7], ovary [8], and lung [9], as well as leukemia [10]. Through directly regulating key target genes, miRNAs can cause phenotypic alterations in tumor cells, thereby mediating tumor resistance to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that transcription disorders, mutations, DNA replication anomalies, and a faulty miRNA biogenesis pathway might be the main reasons for tumor miRNA disorders [10]. For example, the enzyme Dicer, which activates miRNA, and the Argonaute2 protein were significantly downregulated in the Adriamycin-resistant breast cancer cell line MCF-7/DOX.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, miR-224 expression correlated with AML subtypes, in particular the t(15,17) rearrangement, a molecular predictor of favorable clinical outcome [151]. There were additional miRNAs implicated as chemoresistance biomarkers reported in hematological malignancies [152][153][154][155][156][157][158][159][160][161][162].…”
Section: Translating Mirnas Into Clinical Applications In Hematologicmentioning
confidence: 99%
“…To sum up, the researchers predicted that CXCR4‐induced chemoresistance by down‐regulating let‐7a and led to transcriptional activation of MYC and BCLXL in AML cells by YY1 (Chen et al, ). Interestingly, increasing expression of let‐7f in K562 cell lines make the cell more sensitive to adriamycin (Dai et al, ). Recently, a dramatic increase of mir‐19a and mir‐19b expression has been detected in cases receiving the treatment of Vorinostat (histone deacetylase inhibitor‐HDACi).…”
Section: Clinical Significance Of Microrna In Outcome Estimation and mentioning
confidence: 99%